Genetic Origins of the Two Canis lupus familiaris (Dog) Freight Dog Populations. (25th January 2022) - Ali, Muhammad Basil; Dreger, Dayna L; Buckley, Reuben M; Mansoor, Shahid; Khan, Qaiser M; Ostrander, Elaine A
Abstract: Despite periodic drops in popularity, Arctic sled dogs continue to play a vital role in northern societies, providing both freight transit and recreational race activities. In this study, we selected the Mackenzie River Husky, a freight dog of complex history, and the Chinook, an American Kennel Club recognized freight dog breed whose heritage reportedly overlaps that of the MKRH, for detailed population analysis. We tested each to determine their component breeds and used admixture analysis to ascertain their population structure. We utilized haplotype analysis to identify genomic regions shared between each population and their founding breeds. Our data show that the Alaskan Malamutes and modern Greenland sled dog contributed to both populations, but there are also unexpected contributions from the German Shepherd dog and Collie. We used haplotype analysis to identify genomic regions nearing fixation in population type and identify provocative genes in each region. Finally, in response to recent reports regarding the importance of dietary lipid genes in Arctic dogs, we analyzed 8 such genes in a targeted analysis observing signatures of selection in both populations at the MLXIPL gene loci. These data highlight the genetic routes that breeds of similar function have taken toward their occupation as successful sled dogs.